The effect of probiotic and synbiotic supplementation on lipid parameters among patients with cardiometabolic risk factors: a systematic review and meta-analysis of clinical trials. Issue 4 (8th August 2022) - Ghorbani, Zeinab; Kazemi, Asma; U.P. Bartolomaeus, Theda; Martami, Fahimeh; Noormohammadi, Morvarid; Salari, Arsalan; Löber, Ulrike; Balou, Heydar Ali; K. Forslund, Sofia; Mahdavi-Roshan, Marjan
Abstract: Although the available evidence emphasizes the beneficial effects of probiotics in normalizing various cardiometabolic markers, there is still substantial uncertainty in this regard. Thus, we set out to determine the effect sizes of probiotics on blood lipid parameters more coherently. A systematic literature search of the Medline (PubMed) and Scopus databases was conducted from inception to 12 February 2021, applying both MeSH terms and free text terms to find the relevant randomized controlled trials (RCTs). The meta-analysis was conducted based on a random-effect model to calculate the mean effect sizes demonstrated as weighted mean differences (WMDs) and the 95% confidence intervals (95% CIs). To explore the heterogeneity, the Cochrane χ 2 test, and analysis of Galbraith plots were performed. Meta-analysis of data from 40 RCTs ( n = 2795) indicated a significant decrease in serum/plasma triglyceride [WMD (95% CI) = –12.26 (–17.11 to –7.41) mg/dL; P -value <0.001; I 2 (%) = 29.9; P heterogeneity = 0.034], total cholesterol (with high heterogeneity) (WMD (95% CI) = –8.43 (–11.90 to –4.95) mg/dL; P -value <0.001; I 2 (%) = 56.8; P heterogeneity < 0.001), LDL-C [WMD (95% CI) = –5.08 (–7.61, –2.56) mg/dL; P -value <0.001; I 2 (%) = 42.7; P heterogeneity = 0.002], and HDL-C (with high heterogeneity) (WMD (95% CI) = 1.14 (0.23, 2.05) mg/dL; P -value = 0.014; I 2 (%) = 59.8; P heterogeneity < 0.001) following receiving probiotic/synbiotic supplements. Collectively, the current preliminary evidence supports the effectiveness of probiotics/synbiotics in improving dyslipidaemia and various lipid parameters more prominently among subjects with hyperlipidaemia, diabetes, and metabolic syndrome. However, large and well conducted RCTs are required to provide further convincing support for these results.